Experimental design of complement component 5a‐induced acute lung injury (C5a‐ALI): a role of CC‐chemokine receptor type 5 during immune activation by anaphylatoxin. Issue 9 (21st May 2015) - Russkamp, Norman F.; Ruemmler, Robert; Roewe, Julian; Moore, Bethany B.; Ward, Peter A.; Bosmann, Markus
ABSTRACT: Excessive activation of the complement system is detrimental in acute inflammatory disorders. In this study, we analyzed the role of complement‐derived anaphylatoxins in the pathogenesis of experimental acute lung injury/acute respiratory distress syndrome (ALI/ARDS) in C57BL/6J mice. Intratracheal administration of recombinant mouse complement component (C5a) caused alveolar inflammation with abundant recruitment of Ly6‐G + CD11b + leukocytes to the alveolar spaces and severe alveolar‐capillary barrier dysfunction (C5a‐ALI; EC50[C5a] = 20 ng/g body weight). Equimolar concentrations of C3a or desarginated C5a (C5adesArg ) did not induce alveolar inflammation. The severity of C5a‐ALI was aggravated in C5‐deficient mice. Depletion of Ly6‐G + cells and use of C5aR1 ‐/‐ bone marrow chimeras suggested an essential role of C5aR1 + hematopoietic cells in C5a‐ALI. Blockade of PI3K/Akt and MEK1/2 kinase pathways completely abrogated lung injury. The mechanistic description is that C5a altered the alveolar cytokine milieu and caused significant release of CC‐chemokines. Mice with genetic deficiency of CC‐chemokine receptor (CCR) type 5, the common receptor of chemokine (C‐C motif) ligand (CCL) 3, CCL4, and CCL5, displayed reduced lung damage. Moreover, treatment with a CCR5 antagonist, maraviroc, was protective against C5a‐ALI. In summary, our results suggest that the detrimental effects of C5a in this model are partly mediated through CCR5 activation downstream of C5aR1, which may be evaluated for potential therapeutic exploitation in ALI/ARDS.—Russkamp, N. F., Ruemmler, R., Roewe, J., Moore, B. B., Ward, P. A., Bosmann, M. Experimental design of complement component 5a‐induced acute lung injury (C5a‐ALI): a role of CC‐chemokine receptor type 5 during immune activation by anaphylatoxin. FASEB J. 29, 3762‐3772 (2015). www.fasebj.org